'It comes from you': Agency in adult migrants? language learning through process drama - Piazzoli, Erika (Routledge, 2019)
In this paper, we present a study of adult asylum seekers learning Italian as a Second Language through Process Drama. Adopting an ecology of language approach, we first set the scene by examining some of the most salient issues regarding the language learning needs of asylum seekers and refugees, including the challenge of fostering both language proficiency and a sense of autonomy and agency. We then introduce the topic of performative, or dramabased pedagogy, focussing on how this has been adopted for second-language learning, presenting the main features of Process Drama. We go on to evaluate a number of drama-based projects aimed specifically at adult asylum seekers and refugees before presenting the specific context of this study. The Process Drama sessions, organised in the 2016/2107 year, were part of a project called “Cultura e Accoglienza”, which allowed for the enrolment of 30 asylum seekers as “guest students” at the University of Padova in Northern Italy. In particular, we look at one of the Process Drama sessions, in which the participants became members of an association of community workers welcoming migrants, and the teacher took on the role of the asylum seeker. Through the dramatic frame, we, as facilitators, drew on the learners’ expertise in settling into the Italian culture, and in welcoming new arrivals. Our aim was that of using ‘time’, ‘place’ and ‘role reversal’ as distancing devices to challenge the notion of ‘otherness’. The analysis from videos, focus groups and teacher journals suggests that the drama gave participants the chance to shift perspective, and that this impacted on their sense of agency as second language learners.
PUBLISHED
Abingdon, Oxon, UK and New York, USA
Keywords: Asylum seekers; Process Drama; Performative learning; Agency; Reciprocity; Creative Arts Practice; Identities in Transformation; Drama in Education; EDUCATION; PROCESS DRAMA; affective factors in second language learning; Community; Education